FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LABA PERUSAHAAN (Studi pada Perusahaan Industri Dasar dan Kimia yang terdaftar di Bursa Efek Indonesia periode 2014-2016) - Rebecca Antoniette Hadi, 14.05.52.0014; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
The purpose of this study is to examines and analyses the effect of firm size, liquidity, capital structure, managerial ownership, institutional ownership, audit committee, and independent commissioner to earning quality. This research was conducted at base industry and chemical company listed on Indonesia Stock Exchange (BEI). The sampling method used in this study is purposive sampling with observation period 2014 to 2016 the number of samples obtained as much as 48. The influence between variables is discribed by using multiple regression analysis with SPSS 23 program. The type of data used is secondary data. The results showed that the liquidity, capital structure, institutional ownership, and independent commissioner significantly positive affecting the earning quality. While the firm size, managerial ownership, and audit committee do not significantly affect the earning quality.Keywords : firm size, liquidity, capital structure, managerial ownership, institutional ownership, audit committee, and independent commissioner.